(untitled) (Research, Society and Development, 2021)
Objective: The research aims to describe the epidemiological profile of deaths due to ALD between the years 2006 and 2015 in the state of Rio Grande do Sul (RS). Methods: Analysis of DATASUS database and demographic population of each region. The mortality rate was calculated for every 100,000 inhabitants and the analysis was divided into sex (female and male), year (2006 to 2015), age group (0-19, 20-59 and 60+) and macro-regions of RS (Valleys, South, Serra, North, Missionary, Metropolitan and Midwest). Results: The Metropolitan region had the highest total number of deaths (2277 men and 279 women), followed by North, Serra, Midwest and Missioneira Sul. Analyzing the number of deaths per 100,000 inhabitants, the North region had the highest mortality rate. Regarding the sexes, there was a higher prevalence of males with significant difference (p0.012) for the two variables and, regarding the age group, the highest rates were found in the elderly group (60 years or older). Conclusion: ALD remains a condition with a major impact on Brazilian’s public health system. Strategies to improve screening, public policies aimed to prevent the consumption of alcoholic beverages and the epidemiological knowledge of the disease are essential to reduce morbimortality in RS and others brazilian’s states. Incluir o resumo em inglês.